Innovation and competitiveness: Where Latin America is located comparatively according to the indicators (Revista Posgrado y Sociedad, 2020)
It is common to associate innovation with the level of development and competitiveness of a country. The Global Innovation Index makes a classification in this area. For the Latin American countries, the production of patents was studied, the influence of the variables that the index considers in its evaluation and the final classification, as well as the internal behavior of the region and its comparison with the group of 7 (G7). The results show that there is no variable that correlates with the innovation index and that there are very marked differences between the two study groups and even within the Latin American region. This poses very important challenges to achieve an improvement in this aspect, since it also demonstrated a correlation between innovation and competitiveness for industrialized countries that does not present itself for the region.
Keywords: Innovation, competitiveness, Latin America, industrialized, index; innovation; competitiveness; Latin America; industrialized; index